Robot path planning and cooperation : foundations, algorithms and experimentations /: foundations, algorithms and experimentations. ([2018]) - Koubâa, Anis; Bennaceur, Hachemi; Chaari, Imen; Trigui, Sahar; Ammar, Adel; Sriti, Mohamed-Foued; Alajlan, Maram; Cheikhrouhou, Omar; Javed, Yasir
No abstract available